Financial stability in the EU: A case for micro data transparency - Johannes Kasinger; Loriana Pelizzon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
Even if the importance of micro data transparency is a well-established fact, European institutions are still lacking behind the US when it comes to the provision of financial market data to academics. In this Policy Letter we discuss five different types of micro data that are crucial for monitoring (systemic) risk in the financial system, identifying and understanding inter-linkages in financial markets and thus have important implications for policymakers and regulatory authorities. We come to the conclusion that for all five areas of micro data, outlined in this Policy Letter (bank balance sheet data, asset portfolio data, market transaction data, market high frequency data and central bank data), the benefits of increased transparency greatly offset potential downsides. Hence, European policymakers would do well to follow the US example and close the sizeable gap in micro data transparency. For most cases, relevant data is already collected (at least on national level), but just not made available to academics for partly incomprehensible reasons. Overcoming these obstacles could foster financial stability in Europe and assure level playing fields with US regulators and policymakers.
urn:nbn:de:hebis:30:3-457978
Keywords: 330; micro data transparency; financial stability; financial market data